Exploring the Sensory Profile of Stevia Coffee Using Rate-All-That-Apply (RATA) Method and Chemical Analysis - Tarigan, Elsera Br; Hardianti, Cindy Amelia; Rifqi, Muhammad (Indonesian Journal of Applied Research (IJAR), 2024)
Coffee is usually consumed by adding sugar, cream, or milk. Adding these ingredients, especially sugar, can cause new disease problems. The market is starting to look for natural sweeteners that do not cause health problems, such as stevia. The objective of this research was to identify the sensory attributes and chemical components of some variety of stevia coffee formulations. Sensory attributes were identified through a focus group discussion (FGD), and sensory profiling to choose the best formulation was determined using the Rate-All-That-Apply (RATA). The FGD members were nine panelists, while the RATA sensory evaluation used 30 panelists. Chemical analysis carried out includes water (gravimetry), ash (gravimetry), and antioxidant capacity (spectrophotometry). In this research, four distinct formulations of stevia coffee, A1 (0% stevia), A2 (2% stevia), A3 (4% stevia), and A4 (7% stevia), were utilized. Results indicate that varying stevia concentrations significantly influence the resulting coffee's sensory characteristics. Attributes identified through FGD include color (dark brown), aroma (green/leafy, sour, roasted, spicy), taste (acid/sour, sweet, bitter, green, spice) and aftertaste (over, bitter and sweet). Statistical analysis showed that eight out of thirteen sensory attributes had significant differences (p<0.05) among the four samples. Sensory evaluation of the selected sample, A2 (4%), revealed a favorable taste profile characterized by sweetness and sourness. Moreover, the chosen formulation exhibited a notable antioxidant activity level of 83.13%. These findings underscore the potential of stevia coffee as a flavorful and health-conscious alternative, offering valuable insights for product development and consumer acceptance.